Ultrasonic velocities and refractive indies of binary liquid mixtures of 1, 4-dioxane with 1 â€“ alkanols (C3, C4, C6 , C8 ) at 303.15 K - Agarwa, Seema; Kumar Sharma, Dhirendra (International Journal of Advanced Chemistry, 2022)
Density (Ï), ultrasonic velocities (u) and refractive indices (n) of the binary mixture between cyclic ether with 1-propanol, 1-butanol, 1-hexanol, 1-octanol for the entire concentration range have been measured at 303.15K, furthermore, deviation in refractive indies from ideal mixture, molar refraction, deviation in molar refraction from ideal values for these mixture has also been evaluated. The deviations from ideality of the acoustical parameters are explained on the basis of molecular interaction between the component molecules in these binary liquid mixtures. The molecular refraction (Rm), excess molecular refraction ( ) and excess molar volume (VE) were calculated from the experimental data. The results are discussed in term of molecular interactions between the components of the binary mixtures.Â Â Â